Gardening the Amana Way - Rettig, Lawrence L. (Book collections on Project MUSE., 2013)
Gardening in Iowa's Amana Colonies is the culmination of techniques that stretch back several centuries to central Europe, when adherents to a new faith called the Community of True Inspiration formed their own self-reliant communities. As a child of parents who were part of the communal life of the Amana Society, the author pays homage to the Amana gardening tradition and extends it into the twenty-first century. Each of the seven villages in Amana relied on the food prepared in its communal kitchens, and each kitchen depended on its communal garden for most of the dishes served. The author begins by describing the evolution of communal gardening in old Amana, focusing especially on planting, harvesting, and storing vegetables from asparagus to egg lettuce to turnips. With the passing of the old order in 1932, the number of the society's large vegetable gardens and orchards dwindled, but the author and his wife still grow some of the colonies' heirloom varieties in their fourth-generation South Amana vegetable garden. The author extends his gardening advice into the kitchen and workroom. He shares family recipes for any number of traditional dishes, including radish salad, dumpling soup, Amana pickled ham, apple bread, eleven-minute meat loaf, and strawberry rhubarb pie. Moving into the workroom, he shows readers how to make hammered botanical prints, Della Robbia centerpieces, holiday wreaths, a gnome home, and even a waterless fountain.